Effects of an acute bout of static stretching on 40 m sprint performance: Influence of baseline flexibility - Favero, J.-P.; Midgley, A. W.; Bentley, D. J. (Research in Sports Medicine, 2009)
This study investigated the effect of stretching on sprint performance. Ten trained male subjects (age 22 ± 2.3 yrs; body mass 77.1 ± 6.9 kg; height 179 ± 5.5 cm) were randomly assigned to "Rest" and "Stretch" conditions. A low intensity 5 min running warm-up was followed by either 12 min of inactivity (Rest) or lower-limb stretches (Stretch). Subjects walked for 60 s before completing three maximal effort 40 m sprint trials. There were no statistically significant differences in measures of sprint performance between conditions (p > 0.05); however, there was a significant correlation between baseline sit-and-reach scores and mean change in mean velocity between conditions (r = -0.68; p = 0.03). There was a tendency for stretching to negatively effect sprint performance in subjects with comparatively high baseline flexibility. An acute bout of stretching did not exert a significant effect on sprint performance under prescribed conditions